Abusive Supervision dan Peran Perbedaan Gender Karyawan: Sebuah Tinjauan Literatur Sistematis - Andi Andyna Maharezky Edhy; Wiwin Hendriani (EduInovasi: Journal of Basic Educational Studies, 2025)
Abusive supervision becomes an issue or phenomenon in a leadership method. Abusive supervision refers to the subjectivity of employees gives rise to different responses in receiving treatment. This study is a literature review with a systematic approach to examine various responses to the impact of abusive supervision, based on gender differences (male and female) on employees that will trigger an employee's desire to leave the organization. The results of this systematic literature review are differences in responses, where male employees show an attitude that can resist and deal with abusive supervision, so they do not show a tendency to leave the company. Meanwhile, female employees feel the negative impact of abusive supervision, thus assessing abusive supervision as a negative experience that should be avoided, and tend to have more frequent intentions to leave the company.